Prospective revalidation of IOTA “two-step”, “alternative two-step” and “three-step” strategies for characterization of adnexal masses – An Indian study focussing the radiology context - Grover, Shabnam Bhandari; Patra, Sayantan; Grover, Hemal; Mittal, Pratima; Khanna, Geetika (Indian Journal of Radiology and Imaging, 2020)
Objectives: The purpose of this study was to revalidate the diagnostic performance of IOTA “two step” (Simple Descriptors and Simple Rules), “ alternative two step” (Simple Rules Risk Calculation tool / SRrisk score), and three step (two step with subjective assessment) strategies, for characterization of adnexal masses as benign or malignant, using histopathology as gold standard. Materials and Methods: This prospective, study comprised of 100 patients with newly diagnosed adnexal masses, who underwent ultrasound evaluation first by a level I and then by a level III investigator (EFSUMB criteria). Initially, the level I investigator evaluated each adnexal mass, applying IOTA “two-step” strategy and simultaneously assigned a risk category, by applying the simple rules risk score (SRrisk score ) or performing the “alternative two step” strategy. Subsequently the inconclusive masses were evaluated by the level III investigator using “real time subjective assessment”, thereby performing the third step. Following histopathology diagnosis, the performance of each strategy was evaluated using diagnostic tests. Results: The sensitivity, specificity, PPV, NPV, and diagnostic accuracy of “two-step” strategy were 87.5%, 79.2%, 89.4%, 76%, and 84.7%, respectively; those of “alternative two-step” strategy were 91.5%, 75.6%, 84.4%, 86.1% and 88%; and those of “three-step” strategy were 98.2%, 93.3%, 94.7%, 97.7% and 96%, respectively. Conclusion: All IOTA strategies showed good diagnostic performance for characterization of adnexal masses and the “three-step” strategy performed best. We believe this is the first ever prospective re-validation and comparative evaluation of all three IOTA strategies by Indian Radiologists. Since ultrasound is the primary modality for evaluation of adnexal masses, based on the good results of our study, a recommendation for henceforth standard application, of the three-step IOTA strategy in routine Radiology practice appears justified. Although, IOTA strategies been proposed and validated mainly by Gynaecologists and Oncology surgeons, based on the results of our study, this paradigm can now be made to shift back to the arena of Radiology and Radiologists, the imaging experts.
Keywords: adnexal mass; IOTA two step strategy; IOTA alternative two step strategy; IOTA Simple rules risk (SRrisk); IOTA three step strategy